Konsep Karakter Al-Qawiy dan Al-Amin Sebagai Fondasi Kewirausahaan Muda Kontemporer - Abdul Razak; Farid Wajdi; Fitri Kumalasari (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT This library research is motivated by the integrity crisis of the digital era and the imbalance of hard skills without moral maturity among the younger generation. This study aims to formulate the integration of ideal characters using the Thematic Exegesis (Maudhu’i) method on the twin pillars of Al-Qawiy (competence) and Al-Amin (integrity). The primary data refer to Surah Al-Qashas: 26, Surah An-Naml: 39, as well as the authoritative exegesis books of Al-Misbah, Al-Azhar, and Ibn Kathir. A qualitative approach with interpretive hermeneutics is used to synthesize textual meanings into operational indicators. The results show that Al-Qawiy and Al-Amin are universal complementary pillars. The Al-Qawiy character is transformed into professional capability, digital proficiency, and mental resilience. Meanwhile, Al-Amin is manifested in integrity, transparency, and work accountability. The reactualization of these twin pillars is effective as a concrete solution to break structural corruption and business ethics manipulation. This formulation can be adopted as a standard operating procedure (SOP) for the work ethics of young entrepreneurs and academic instructional materials. Keywords : Al-Amin; Al-Qawiy; Entrepreneurship; Professional Integrity; Thematic Exegesis